The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1037/tra0000005
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of posttraumatic growth and depreciation after two major earthquakes.

Abstract: This study examined trajectories of posttraumatic growth or depreciation (i.e., positive or negative life change) in personal strength and relationships after 2 major earthquakes in Canterbury, New Zealand using group-based trajectory modeling. Participants completed questionnaires regarding posttraumatic growth or depreciation in personal strength and relationship domains 1 month after the first earthquake in September 2010 (N = 185) and 3 months (n = 156) and 12 months (n = 144) after the more severe Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 50 publications
6
51
1
Order By: Relevance
“…Community‐level analyses showed that areas with higher levels of group involvement offered greater post‐disaster mental health protection.13. Marshall et al () Modelled post‐traumatic growth and posttraumatic depreciation trajectories.Events: Canterbury earthquake, September 2010; Christchurch earthquake, February 2011 Country: New Zealand Age: adults (mean=56.80) Sample size: 156 Sampling: random Diversity: 75 per cent female; 91 per cent New Zealand EuropeanDesign: prospective, longitudinal Time: two months before; 1, 3, and 12 months after Support measures: post‐disaster relationship functioning (five items; scale‐based)Group‐based trajectory modelling revealed that all participants reported some degree of growth in post‐disaster personal relationships ( support growth ). This effect was stronger among females.14.…”
Section: Annexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Community‐level analyses showed that areas with higher levels of group involvement offered greater post‐disaster mental health protection.13. Marshall et al () Modelled post‐traumatic growth and posttraumatic depreciation trajectories.Events: Canterbury earthquake, September 2010; Christchurch earthquake, February 2011 Country: New Zealand Age: adults (mean=56.80) Sample size: 156 Sampling: random Diversity: 75 per cent female; 91 per cent New Zealand EuropeanDesign: prospective, longitudinal Time: two months before; 1, 3, and 12 months after Support measures: post‐disaster relationship functioning (five items; scale‐based)Group‐based trajectory modelling revealed that all participants reported some degree of growth in post‐disaster personal relationships ( support growth ). This effect was stronger among females.14.…”
Section: Annexesmentioning
confidence: 99%
“…Major social support findings 13. Marshall et al (2015) Modelled post-traumatic growth and posttraumatic depreciation trajectories. Analyses that accounted for covariates showed that respondents with high PTSD score (PCL-C≥30) 3 at T1 received more social support (support mobilisation-relative needs).…”
Section: Research Design and Social Support Assessmentmentioning
confidence: 99%
“…The findings suggest that some youths (25%) recovered over time, while in others PTSS remained stable either at high (4%) or low levels (71%; Self‐Brown et al., ). Other recent studies have examined the trajectories of PTG over time (Danhauer et al., ; Marshall et al., ). A study of adults after two major earthquakes identified three trajectories of growth in relationships.…”
mentioning
confidence: 99%
“…A study of adults after two major earthquakes identified three trajectories of growth in relationships. They differed only in levels of growth (low, moderate, and high), but no significant change (slope) was observed over time (Marshall et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation